Rethinking Educational Practices: Handwriting and Its Role in Multisensory Language Learning - Rejeki, Sri; Angela Bayu Pertama Sari; Dwi Iswahyuni; Devita Widyaningtyas (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Rapid development of digital technology has changed the educational practices, including the way students learn languages. This research aims to explore perceptions, experiences and challenges faced by the students in using handwriting as a part of multisensory learning strategy in online English class. This research employs convergent mix method whereas the data were gathered from 21 university students majoring in Information system through Likert scale questionnaire and open ended questions. The result of statistics and thematic analysis shows that most of respondents felt the cognitive benefits from handwriting, including improved memory, focus, grammar comprehension and learning engagement. Regression analysis showed that feeling comfort in handwriting has significant positive impact on memory ability; while challenges, including feeling tired and time required do not significantly reduce its cognitive benefits. This research supports multisensory learning theory (VAKT) and strengthen previous findings which showed that handwriting activates wider brain networks compared with typing. Last but not least, handwriting remains relevant in digital era and recommended to be integrated equally in online learning as a part of effective and holistic learning strategy.